"Powered by whom?" : A network perspective on replication as strategy - Mota, João (2022)
This study examines the configuration of resources and activities among firms as a strategy to improve their position in a network through the replication of a template. The conceptual background combines the network approach to strategizing with the capability approach to replication. Using a longitudinal study of a large wholesaler, this study demonstrates that change in a network position can result from two interwoven processes: the development and replication of a template in some sections of the network, and a rearrangement of the web of relationships among counterparts